Исследование памятников Картамышского археологического микрорайона в Донбассе - Бровендер, Ю.М.; Загородняя, О.Н.; Ключнева, И.Н. (Археологічні дослідження в Україні, 2009)
The results of the research of monuments in Kartamysh archaeological micro-region in Donbas are published. In 2008, the excavations covered the technogenic area of the mine Chervone Ozero I, at Chervone Ozero 1 and Chervone Ozero 3 settlements, and at the cape-shaped area near the mine Chervone Ozero IV. Also the experiments in modelling of metallurgic circle were ongoing successfully.